Nushuz Perspektif Alquran: Studi Komparatif Penafsiran Al-Qurṭubi Dan Muhammad Quraish Shihab - Yana Mujayana; Adib Adib; Umayah Umayah (UIN Siber Syekh Nurjati Cirebon, 2018)
The possible cause of divorce is the happening of nushuz from wife (party/side) and also husband. As for wife, nushuz is explained by at Q.S. al-Nisa‘ [4] sentence 34 and nushuz from husband at Q.S. al-Nisa‘ [4] sentence 128. This paper explain the view of al-Qurtubi and M. Quraish Shihab cited from al-Jami' Li Ahkam al-Qur‘an and Tafsir al-Misbah by considering the nowadays context particularly about gender equality as a means to revisit the concept in al-Qur'an about nushuz. The research belongs to library research. The data are managed using descriptive method in the form of comparative method and is also related to the perspective of gender equality in the concept of nushuz of wife as well as husband.